Tanggung Jawab Hukum Klinik Pratama dalam Pengelolaan Limbah Medis: Legal Responsibility of Primary Healthcare Clinics in Medical Waste Management - Dwitasari, Verani; Adriano, Adriano; Noor, M. Tauchid (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
Primary healthcare clinics are among the healthcare facilities that generate medical waste. This medical waste is classified as hazardous and toxic waste (B3), which poses significant risks to human health and the environment if not properly managed. Therefore, primary healthcare clinics are legally required to manage their medical waste in compliance with the applicable laws and regulations. This study aims to analyze the legal framework and forms of legal responsibility of primary healthcare clinics in managing medical waste. A normative juridical method is employed, utilizing statutory and conceptual approaches. The findings reveal that medical waste management in primary healthcare clinics still relies on general provisions regarding B3 waste management and on regulations applicable to healthcare facilities in general. To date, there are no specific legal provisions governing detailed procedures for medical waste management in primary healthcare clinics, creating a legal gap that may contribute to non-compliance in waste management practices. Such non-compliance may lead to legal consequences in the form of administrative, civil, and criminal sanctions. Legal responsibility may be imposed on individuals or legal entities, depending on the organizational form of the primary healthcare clinic.